Taste of asean: traditional food images from Southeast Asian countries - Fajar Kusnadi Kusumah Putra; Mandradhitya Kusuma Putra; Selvi Novianti (Journal of Ethnic Foods, 2023)
Abstract Gastronomy tourism and local food have become a powerful tool for tourism advertising because gastronomy often reflects the cultural identity of the destination. Local food images can help showcase the unique flavors of a particular region, making it more attractive to potential visitors. This study aims to analyze how regional tourism authorities share information about the diversity of traditional foods, promote gastronomic tourism, and enhance destinations' competitiveness by utilizing Instagram as a social media platform combining images with textual information. The ASEAN Tourism Online objectives are to promote the region as a single destination, increase tourism arrivals and receipts, and enhance regional connection. In this study, the official account of Southeast Asia Tourism on Instagram @visitsoutheastasiaofficial with keywords Taste of ASEAN marketing campaign. A qualitative approach using content analysis was used in this study. Data for this study were retrieved from 123 traditional food images posted on the official Instagram account from 2016 to 2022. A thematic analysis was used to classify themes. The findings presented categories ranging from the authenticity of traditional food, social media campaigns and promotions, local destination information, and gastronomic tourism activities. The majority of images posted related to the portrait of local cuisines. This analysis portrayed how the ASEAN tourism online wants to promote food as an attraction instead of food as a supporting element of tourism activities. The limitation of this study is only focused on the content of traditional visual food on the Instagram platform. Further research can be done using other social media platforms and comparing these findings with other destinations. It also provides an opportunity to gain insights into what people are saying about each destination, which can be helpful in terms of understanding customer preferences and opinions. The implication of this study will help national tourism organizations, culinary practitioners and academicians about the traditional food images on the social media platform to promote regional and city tourism. Additionally, it can help to identify potential opportunities for improvement or expansion within the region. Finally, researching other destinations through social media platforms can provide valuable information that could be used to create effective marketing strategies and campaigns.